FREQUENCY OF GALLSTONES IN PATIENTS WITH LIVER CIRRHOSIS - Hussain, Azhar; Nadeem, Muhammad Arif; Nisar, Sajid; Tauseef, Hafiza Ammarah (Journal of Ayub Medical College Abbottabad, 2014)
Background: Liver cirrhosis is a serious disease which can lead to liver failure. The main objective of this study was to ascertain the frequency of gallstones in patients with liver cirrhosis. Methods: One hundred and fifty patients fulfilling the inclusion criteria were selected from Medical Unit-IV for this cross sectional study. Their abdominal ultrasound was done to diagnose liver cirrhosis and to see presence of gallstones. All the patients were assessed by same sonologist. Their demographic data was entered in a specially designed pro forma. Results: Frequency of gall stones in patients with liver cirrhosis was found to be 21.6%. Conclusion: This study reveals that the gallstones are frequent in patients suffering from chronic liver disease. The frequency of gallstones increases with increase in disease duration. Keywords: Cirrhosis, Gallstones, Fibrosis, Chronic liver disease